What can Twitter tell us about social movements' network topology and centrality? Analysing the case of the 2011–2013 Chilean student movement. (1st January 2014) - García, Cristóbal; Bülow, Marisa von; Ledezma, Javier; Chauveau, Paul
We analyse the Chilean student movement by looking at Twitter data from 26 protests, distributed between May of 2011 and November of 2013. Using a mixed methods approach, based on social network analysis and qualitative methods, this article uncovers specific Twitter-based protest patterns and changing centrality of actors over time. It finds that the student movement has increasingly used Twitter, especially during days of protest. It also identifies a process of Twitter institutionalisation, whereby official accounts of organisations have become more central through time, in comparison with individual leaders' accounts. This article contributes to the literature that analyses how existing social movement organisations adapt to emerging environments of digital activism.